Dietary tributyrin, an HDAC inhibitor, promotes muscle growth through enhanced terminal differentiation of satellite cells. Issue 10 (23rd May 2018) - Murray, Robert L.; Zhang, Wei; Iwaniuk, Marie; Grilli, Ester; Stahl, Chad H.
Abstract: Muscle growth and repair rely on two main mechanisms – myonuclear accretion and subsequent protein accumulation. Altering the ability of muscle resident stem cells (satellite cells) to progress through their myogenic lineage can have a profound effect on lifetime muscle growth and repair. The use of the histone deacetylase (HDAC) inhibitor, butyrate, has had positive outcomes on the in vitro promotion of satellite cell myogenesis. In animal models, the use of butyrate has had promising results in treating myopathic conditions as well as improving growth efficiency, but the impact of dietary butyrate on satellite cells and muscle growth has not been elucidated. We investigated the impact of tributyrin, a butyrate prodrug, on satellite cell activity and muscle growth in a piglet model. Satellite cells from tributyrin‐treated piglets had altered myogenic potential, and piglets receiving tributyrin had a 40% increase in DNA:protein ratio after 21 days, indicating the potential for enhanced muscle growth. To assess muscle growth potential, piglets were supplemented tributyrin (0.5%) during either the neonatal phase (d1–d21) and/or the nursery phase (d21–d58) in a 2 × 2 factorial design. Piglets who received tributyrin during the neonatal phase had improved growth performance at the end of the study and had a 10% larger loin eye area and muscle fiber cross‐sectional area. Tributyrin treatment in the nursery phase alone did not have a significant effect on muscle growth or feed efficiency. These findings suggest that tributyrin is a potent promoter of muscle growth via altered satellite cell myogenesis. Abstract : We found that dietary tributyrin supplemented to a neonatal piglet increased myonuclear accretion and resulted in enhanced muscle growth. The resulting increase in muscle size can be attributed to the significant increase in the fiber hypertrophy. Tributyrin inclusion seems to have also had a programming effect on satellite cells; cells from treated animals showed an increased capacity to differentiate and form myotubes, most likely through an upregulation of the terminal differentiation process, highlighted by increased myogenin expression.